Honey Dew melon (Cucumis melo L.) grown under greenhouse conditions: correlation among plant density and yield variables - Díaz-Alvarado, Jorge Manuel (2021)
For Honey Dew melon grown under greenhouse conditions and managed with three pruning systems (1-stem; 2-stem; no pruning), the researchers estimated Pearson correlations among plant density and the following variables:  days to start of harvest, fruit weight, number of fruits per plant and per square meter, yield per plant and per area, fruit flesh firmness and percentage of total soluble solids.  The crop was planted on coconut fiber as substrate, and managed with fertigation.  For all three pruning systems, the Pearson correlations that were statistically significant (p ≤ 0,05), were obtained between plant density and:  total number of fruits per plant (r = –0,65**); number of commercial fruits per plant (r = –0,65**); total yield per plant (r = –0,69**); and commercial yield per plant (r = –0,69**); in those cases the linear regression was calculated.  For 2-stem pruning treatments, a significant correlation was obtained between plant density and percentage of total soluble solids (r = –0,64*).  For no pruning treatment, a significant correlation was obtained between plant density and days to start of harvest (r = 0,98**).  It is concluded that in Honey Dew melon managed with any of the evaluated pruning systems, the use of a higher plant density lead to a decrease in the number of fruits (total and commercial) per plant, and in the total and commercial yield per plant.